Perceptions of Police Among Hispanic Immigrants of Mexican Origin in the Southeast United States - Roles, Rocio (American journal of criminal justice, 2016)
Studies have repeatedly shown that members of minority groups are likely to hold less favorable perceptions of the police than their white counterparts. Relying on a unique sample of nearly 70 Hispanic immigrants, this study expands current knowledge on correlates of Hispanics’ perceptions of police. Overall, findings of this study indicate Hispanic immigrants of Mexican descent generally hold favorable views of the police. Results also suggest, however, that those who came to the US through illegal channels are significantly less likely to hold positive perceptions of police than those who relocated through legal channels. Furthermore, a preliminary analysis to assess the level of understanding that Hispanic immigrants have of police, including their role and function in American society, was conducted. Findings indicate there is a high level of misunderstanding concerning police services among this population. Based on our results, we discuss policy implications and future directions for research.